The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.11606/s1518-8787.2021055002395
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e percepção sobre modelos de rotulagem nutricional frontal no Brasil

Abstract: OBJETIVO: Avaliar o desempenho e a percepção de cinco modelos de rotulagem nutricional frontal (RNF) entre consumidores brasileiros. MÉTODOS: Estudo transversal, com aplicação de questionário online a 2.400 indivíduos, alocados de forma aleatória em seis grupos de estudo, sendo um controle e cinco expostos a modelos de RNF (octógono, triângulo, círculo, lupa e semáforo), aplicados a nove alimentos. Foi avaliado o entendimento do conteúdo nutricional, a percepção de saudabilidade, a intenção de compra e a perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
1
10
0
7
Order By: Relevance
“…These findings show that the presence of FoPNL favors the better interpretation of the nutritional content of the product, a finding also seen in other studies (9,14,17). An online study carried out in 2021 with 2400 Brazilian participants also indicated that the use of different FoPNL models, including the magnifying glass and the octagon, both increased the understanding of the nutritional content of products, but this studies evaluated the effectiveness of the design only and not the concomitant application of nutritional profile models (26).…”
Section: In Your Opinion Does the Scanned Product Contain Any Excessi...mentioning
confidence: 99%
“…These findings show that the presence of FoPNL favors the better interpretation of the nutritional content of the product, a finding also seen in other studies (9,14,17). An online study carried out in 2021 with 2400 Brazilian participants also indicated that the use of different FoPNL models, including the magnifying glass and the octagon, both increased the understanding of the nutritional content of products, but this studies evaluated the effectiveness of the design only and not the concomitant application of nutritional profile models (26).…”
Section: In Your Opinion Does the Scanned Product Contain Any Excessi...mentioning
confidence: 99%
“…Moreover, the red signal labeling has been shown to potentially reduce unhealthy eating habits and activate the superior medial frontal gyrus and accessory motor area. Additionally, online surveys from other countries that do not have an FOPL have reported the usefulness of applying nutrition la-bels [35]. In the future, it would be useful to conduct an attribution analysis on the impact of TLF labels on Japanese consumers because there are reports that TLF use and nutrition-al knowledge are related to the socioeconomic and educational status of the participants [16].…”
Section: Discussionmentioning
confidence: 99%
“…Results are also expected to contribute to the evaluation of the effect of graphical design on the effectiveness of warning labels, a topic that has been increasingly receiving more attention in the literature more recently. [33][34][35][36][37][38][39] The hypotheses tested in the study include: (1) OWL, MGG and TFL improve consumers' ability to correctly identify the least harmful product more often; (2) these FOP labelling schemes improve Open access consumers' ability to correctly identify the presence of excessive nutrient content in products more often; (3) and these FOP labelling schemes increase consumers' intention to purchase the least harmful option or none of the options of a series of products, more often. These hypotheses have been tested both against the control condition, and between the FOP labelling schemes, to verify whether there is a scheme that performs differently from the others for each hypothesis.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The comparisons aimed at assessing the effect of these FOP labelling schemes on objective understanding (correct identification of the least harmful product and correct identification of excessive nutrient content), and intention to purchase of a series of products, in Jamaica. Results are also expected to contribute to the evaluation of the effect of graphical design on the effectiveness of warning labels, a topic that has been increasingly receiving more attention in the literature more recently 33–39. The hypotheses tested in the study include: (1) OWL, MGG and TFL improve consumers’ ability to correctly identify the least harmful product more often; (2) these FOP labelling schemes improve consumers’ ability to correctly identify the presence of excessive nutrient content in products more often; (3) and these FOP labelling schemes increase consumers’ intention to purchase the least harmful option or none of the options of a series of products, more often.…”
Section: Introductionmentioning
confidence: 99%